Deciphering the gamma-ray emission in the Cygnus region - Härer, Lucia; Vieu, Thibault; Schulze, Florian; Larkin, Cormac; Reville, Brian (Astronomy and astrophysics, 2025)
The Cygnus region is a vast star-forming complex harbouring a population of powerful objects, including massive star clusters and associations, Wolf-Rayet stars, pulsars, and supernova remnants. The multi-wavelength picture is far from understood, particularly the recent LHAASO detection of multi-degree scale diffuse γ-ray emission up to PeV energies. We aim to model the broadband γ-ray data, discriminating plausible scenarios amongst all candidate accelerators. We consider in particular relic hadronic emission from a supernova remnant expanding in a low-density environment and inverse Compton emission from stellar-wind termination shocks in the Cygnus OB2 stellar association. We first estimated the maximum particle energy from a 3D hydrodynamical simulation of the supernova remnant scenario. The transport equation was then solved numerically to determine the radial distribution of non-thermal protons and electrons. In order to compute synthetic γ-ray spectra and emission maps, we developed a 3D model of the gas distribution. This includes, firstly, a HI component with a low-density superbubble around Cygnus OB2 and, secondly, molecular clouds lying at the edge of the superbubble and in the foreground. We find that a powerful ~50 kyr-old supernova remnant can account for both the morphology and spectrum from 10 TeV-PeV. At PeV energies, the microquasar Cygnus X-3 and diffuse galactic cosmic rays might also contribute to the flux. Below about 10 TeV, hadronic models are incompatible with the expected existence of a superbubble centred on Cygnus OB2. Instead, the spectrum is well fitted with inverse Compton emission from electrons accelerated at stellar-wind termination shocks in Cygnus OB2, which is in line with existing multi-wavelength limits.
Gesehen am 25.02.2026